(untitled) (VERUM: Journal of Scientific Initiation, 2026)
This article presents partial reflections from an ongoing study on the right to adequate housing in the post-disaster context of the 2024 floods in Colônia Z3, Pelotas/RS. Grounded in Southern epistemologies, the study examines how territorial reconstruction reveals symbolic and political disputes, exposing structural inequalities and state selectivity. The methodology combines documentary analysis, exploratory research, and semi-structured interviews, with an emphasis on qualitative listening. Preliminary findings, based on interviews with residents, highlight institutional abandonment, community resilience, and the inadequacy of housing solutions, analyzed in light of constitutional norms and recent case law. It concludes by emphasizing the need for participatory reparations that recognize territory as a space of dignity and resistance, with practical application of laws such as the City Statute and the National Policy on Protection and Civil Defense.